Emotions and Instructed Language Learning: Proposing a Second Language Emotions and Positive Psychology Model - Shao, Kaiqi; Nicholson, Laura J.; Kutuk, Gulsah; Lei, Fei (Frontiers in Psychology, 2020)
Although emotion research and positive psychology (PP) have recently gained strong momentum in the field of second language acquisition (SLA), theoretical models linking language emotion and PP research, which offer insights for both research and intervention practice are lacking. To address this gap, the present article first introduces the origin, concept, and research around PP. Next, it summarizes recent research on PP and emotions in SLA. Finally, by triangulating emotion theories and research in the fields of psychology, education, and SLA, we propose a new model, which merges the three pillars of PP (positive institutions, positive characteristics, and positive emotions) with the antecedents, outcomes, and interventions of second language (L2) emotions (the L2EPP model). The value of the model to L2 pedagogy and research is highlighted in the context of the importance of integrating PP into the area of emotions and instructed SLA.